(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The dimensions of safety and sustainability are important for the banking sector as they help expand the participation of banks in various economic activities to advance the economic reality of any country and direct capital towards investments. From this standpoint, the research aims to study and analyze the statistical relationship between the dimensions of safety, represented by (quality of services, liquidity, revenues). Profitability, capital adequacy) and the financial dimension of sustainability, which includes indicators (market value, return on share, deposit growth, credit growth).The importance of the research is demonstrated by helping the bank’s management in ensuring its financial solvency to achieve safety and sustainability. The Middle East Bank was chosen as a sample for the research and its case study due to the availability of its financial data in the stock market. Mathematical equations were used to extract the financial ratios for the research variables based on the bank’s annual reports. The regression method and the Pearson coefficient were used to find the relationship of influence and correlation between the independent and dependent variables and to extract the statistical values for the coefficient of determination (R) and the t-test. The most important conclusions reached by the researcher was that the bank was maintaining a high percentage of liquidity compared to the standard ratio due to its conservative policy. In investing funds, which affected the size of the returns achieved, as was shown from the results of the statistical analysis that the majority of safety dimensions did not have a moral impact on the financial dimension of sustainability, with the exception of the quality of services, which had an impact and correlation on the market value and return on the share. The most important recommendations were to direct management The bank seeks to ease credit restrictions in the granting process and exploit available liquidity to diversify the investment portfolio to improve the bank’s performance, increase the volume of returns, and enhance the market value in the market.